Variable Outcome of Acute Viral Hepatitis in Diabetic and Non Diabetic Patients - Syed Mir Usman Shah, Arif Mumtaz, Hafiz Ud Din, Qaisar Ali Khan, Hefsa Qamar, Mohammad Hanif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to evaluate the clinical and biochemical parameters among patients of acute viral hepatitis in diabetic and non-diabetic cases. Study Design: Observational/Prospective study Place and Duration: In the department of Medicine, Northwest General Hospital & Research Centre, Hayatabad Peshawar and DHQ and Teaching Hospital KDA, Kohat during the period from January, 2021 June, 2021. Methods: There were one hunded and eight cases of acute viral hepatitis were included in this study. Included cases were aged between 18-65 years. A patient's demographic information, such as age, gender, BMI (Body Mass Index), residence, and education status, was collected once the patient provided written consent and informed consent was obtained. Patients categorized in two groups. Group I had 54 diabetic patients and group II had 54 non diabetic patients with AVH. Smoking history and etiology among both groups were assessed. Patients’ clinical and biochemical parameters were evaluated during hospital stay among both groups. SPSS 22.0 was used to analyze all data. Results: There were 72 (66.7%) males and 38 (33.3%) females among 108 cases. In group I mean age was 42.13±6.45 years with mean BMI 25.11±6.34 kg/m2 while in group II mean age was 39.88±11.56 years and had mean BMI 24.7±14.62 kg/m2. Majority of the cases among both groups were from urban areas 32 (59.3%) and 28 (51.9%) cases. There were 35 (64.9%) patients were married in group I and in group II 30 (55.6%) patients were married. Among both groups 25 (46.3%) and 29 (53.7%) patients were literate. Hepatitis E was the most common etiology among both groups followed by B and A. ALT and albumin levels were substantially lower in diabetics than nondiabetics, while mean blood bilirubin levels were significantly higher in diabetics than nondiabetics. Hospital stay in diabetic patients was also greater than that of non-diabetic patients with p value <0.05. Mortality in group I was 2 (3.7%) because of liver failure and in group II there was not any mortality found. Conclusion: According to the results of the current study, diabetic individuals with AVH had lower ALT levels, higher bilirubin levels, a greater risk of liver failure, and longer hospital stays than non-diabetics.